Exposure to essential and non-essential trace elements and risks of congenital heart defects: A narrative review - Liang, Yipu; Pan, Zijian; Zhu, Mingzheng; Gao, Ruonan; Wang, Yijue; Cheng, Yijuan; Zhang, Nannan (Frontiers in Nutrition, 2023)
Congenital heart defects (CHDs) are congenital abnormalities involving the gross structures of the heart and large blood vessels. Environmental factors, genetic factors and their interactions may contribute to the pathogenesis of CHDs. Generally, trace elements can be classified into essential trace elements and non-essential trace elements. Essential trace elements such as copper (Cu), zinc (Zn), iron (Fe), selenium (Se), and manganese (Mn) play important roles in human biological functions such as metabolic function, oxidative stress regulation, and embryonic development. Non-essential trace elements such as cadmium (Cd), arsenic (As), lead (Pb), barium (Ba), and mercury (Hg) are harmful to health even at low concentrations. Recent studies have revealed potential role of these trace elements in the pathogenesis of CHDs. In this review, we summarized current studies exploring exposure to essential and non-essential trace elements and risks of CHDs, in order to provide further insights for the pathogenesis and prevention of CHDs.